Latent profile analysis of psychological needs thwarting in Chinese school teachers: longitudinal associations with problematic smartphone use, psychological distress, and perceived administrative support - Liao, Xiao-Ling; Cao, Cui-Hong; Gamble, Jeffrey H.; Li, Ling-Ling; Jiang, Xing-Yong; Bo, Cun-Xu; Chen, I-Hua (Frontiers in Public Health, 2023)
Considering the significant impact of teachers on education and student growth, their mental health deserves special attention. Due to the popularity of ICT and the promotion of online teaching during the pandemic, this is prone to developing problematic smartphone use (PSU). Psychological need thwarting (PNT) has been shown to be closely related to PSU, psychological distress, and perceived administrative support. However, previous studies primarily adopted a variable-centered approach, potentially overlooking the fact that three basic needs might not be closely associated and could form distinct profiles. Therefore, this study aims to apply latent profile analysis to delineate different PNT profiles and their associations with the aforementioned 3 factors. Using convenient and purposive sampling methods, a longitudinal survey was conducted with 1,642 primary and middle school teachers over a two-month interval (Time 1: November 2021 and Time 2: January 2022). The results indicate that a three-profile model, intricately based on the PNT data gathered at Time 1, is most optimal: Class 1 is labeled as 'High autonomy-High competence and Moderate relatedness thwarting', Class 2 as 'High autonomy-High competence and High relatedness thwarting', and Class 3 as 'Low psychological needs thwarting'. Distinct associations were observed among three profiles concerning PSU, psychological distress, and administrative support. Specifically, Regarding PSU, the score of Class 2 was higher than Class 1, with that of Class 3 being the lowest at Time 1, while at Time 2 no significant difference was found between any two of these three groups; in terms of distress, the scores of the three profiles were arranged from high to low as Class 2, 1, and 3 at both time points; and in terms of perceived administrative support, the order was just the opposite, with 3, 1, and 2 from high to low at both Time 1 and Time 2. Notably, the unchanged order of the three classes in terms of psychological distress and administrative support suggests a lasting influence of PNT. Future studies are encouraged to delve deeper into this enduring impact by employing additional longitudinal data sets and examining potential mediators or moderators beyond the scope of the current study.